The prophethood (Al-Nubuwwah): its necessity and relevance for human life & society - Machouche, Salah (International Institute of Islamic Thought (IIIT) (East and Southeast Asia), 2017)
Prophethood is one of main principle of faith in Islam. Allah defined believers by those who believe in Him, His angles, His scriptures, His messengers and the Day of Resurrection (Qur’an: 2, 285). Prophethood denotes individuals who receive divine revelation and their collective preaching of over the span of human history. In Islam, the origin of prophethood can be retraced back to the first human Adam (AS) who was charged to worship Allah alone. Before sending him down to the earth, Adam was informed that if his guidance is followed, he should not go astray nor suffer from unhappy life (Qur’an, 20: 123). To enable him to fulfill this task, Allah Almighty bestowed Adam with special characteristics, faculties and abilities including: innate knowledge, thinking faculties, and senses. Adam was also granted freewill so that he would make free, voluntary and conscious decisions, good or bad (Qur’an: Balad: 10) to complete his journey in this life. In this context, prophethood is considered as another level of Allah’s guidance which continuously reminding humans about their ultimate task in this life and showing them the right path to achieve it through right belief system (‘Aqidah), right rules (Shari‘ah), right manners (Akhlaq), and true knowledge about their existence (life and hereafter). Allah the Almighty revealed to large number of men (Prophets and Messengers), which are told to be close to 224.000 prophet and 300 messengers.